Clinical Profile of Young-Onset Ischemic Stroke: An Observational Study from a Tertiary-Level Hospital in Kathmandu, Nepal - Koirala, Sunil Ram; Bastola, Pradeep; Pandey, Poonam; Yadav, Shree Narayan; Gupta, Rajesh Kumar (Journal of National Heart and Lung Society Nepal, 2024)
Background: Stroke is the second leading cause of mortality and the third leading cause of disability worldwide. The incidence of stroke among young adults is on the rise. However, data on young stroke patients in the Nepalese population remain limited. This hospital-based study aimed to evaluate the clinical profile and risk factors in young adults presenting with ischaemic stroke. Methods: We retrospectively analysed all available records of patients with ischaemic stroke admitted to the National Academy of Medical Sciences, Bir Hospital, between 1 July 2022 and 30 June 2023. A diagnosis of ischaemic stroke was established when neurological deficits were accompanied by corresponding abnormalities on brain computed tomography (CT) and/or magnetic resonance imaging (MRI). Clinical characteristics and associated risk factors were assessed. Results: Of the 297 patients with ischaemic stroke, 158 (53.2%) were male and 139 (46.8%) were female. The mean age was 64.23 years (SD 15.90), ranging from 25 to 99 years. Fifty-one patients (17.2%) were aged ≤45 years. The most common risk factor was smoking (76.4%), followed by hypertension (72.1%), dyslipidaemia (14.1%), diabetes mellitus (11.1%), atrial fibrillation (8.4%), rheumatic heart disease (5.1%), and dilated cardiomyopathy (1.3%). Conclusion: Conventional risk factors-such as hypertension, dyslipidaemia, smoking, and diabetes mellitus-were prevalent in both young and older stroke patients. Rheumatic heart disease and dyslipidaemia were more common in younger patients, whereas atrial fibrillation and significant carotid stenosis predominated among older patients. Greater emphasis on the prevention and management of modifiable risk factors is essential to reduce the burden of stroke.